Laser patterning of amorphous silicon thin films deposited on flexible and rigid substrates. Issue 7 (1st February 2016) - Alpuim, P.; Cerqueira, M. F.; Iglesias, V.; Machado, G.; Borme, J.
Abstract : The possibility of direct writing thin semiconductive channels and structures on insulating substrates in a clean room‐free process is attractive for its simplicity, cost effectiveness, and possibility of a wide choice of substrates. A broad range of applications, such as large‐area electronic devices (touch screens, flexible displays), sensors, or optical wave guides could benefit from such a process. In this work, we directly write on doped hydrogenated amorphous silicon (a‐Si:H), with thickness in the range 10 nm–1 μm, using a Nd‐YAG laser operating at 532 nm that is part of a Witec Raman confocal system. The contrast in conductivity between the exposed and unexposed areas is so high that the a‐Si:H matrix needs not to be removed after exposure. B‐ and P‐doped films were deposited on plastic, glass, and oxidized silicon wafers. The laser power threshold for crystallization was studied. The highest conductivity (886 Ω −1  cm −1 ) was obtained on wafer. On hard substrates, it is possible to tune the mesoscopic electrical conductivity in a very broad range of values (∼10 −4 –10 3 ) by design of the pattern to be transferred. Patterned films are piezoresistive with gauge factors as high as +18 and −29 for p ‐ and n‐type patterns, respectively. SEM image of laser written lines on a 10 nm thick a‐Si:H film deposited on a Si/SiO2 substrate. Four regions are clearly distinguishable: the metal contact on the top area; the laser eroded area (lines); the crystallized areas adjacent to lines; the amorphous region at the bottom right.